(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: INTERPOL has undergone a series of reforms in the past 8–9 years. Whilst improving the transparency and accountability of the organisation, the areas of finance, technology, the CCF and diversity of the senior executive require further reform. The article aims to further explore why these issues should be a priority for INTERPOL in the short term. Methodology: The article reviews recent INTERPOL news releases and outcomes of recent General Assembly resolutions to further develop the case for further reforms of INTERPOL activities. A review of material generated by NGO’s and other interested parties is also included. Findings: INTERPOL faces unprecedented challenges in a complex global environment. To successfully navigate this complexity, INTERPOL will need addressing three vital areas of operation. First, INTERPOL will need to restructure its budget and secure increased permanent funding to enable the renewal of its information technology infrastructure. Second, it needs to reform the CCF as a vital enabler for the continued issuance of red notices. Third, INTERPOL will have to address these shortcomings in its senior executive diversity. Value: A more comprehensive understanding of the issues that INTERPOL currently faces will ultimately assist policy makers. The understanding of the inherent weakness in the INTERPOL budget structures will assist governments to consider alternative funding models. Similarly, INTERPOL is required to be at the forefront of developing world leading information solutions to law enforcement including border agencies. Lastly, INTERPOL requires the support of all 195 member countries to continue to have international legitimacy in key policy forums. Senior executive representation constitutes a vital component.